Layanan Jasa Keuangan Perbankan Kepada Penyandang Disabilitas di Era "ŽDigital Industri 5.0"Ž (Journal of Dissability Studies and Research (JDSR), 2023)
The government has the responsibility to ensure that every citizen obtains quality banking services according to his needs. Prospective Bank customers from groups of Persons with Disabilities have the right to receive banking financial services on their personal behalf. The right to be independent in financial matters is guaranteed under Law no. 8 of 2016 concerning Persons with Disabilities and OJK Regulation No: 1/POJK.07/2013 concerning Consumer Protection in the Financial Services Sector. The services provided by the banking sector must of course make it easier for persons with disabilities to enjoy every service that exists in the banking service system. This digital era can make it easier for banking financial service providers to provide optimal services. In this digital era, this is a step that can increase innovation in the provision of financial services, especially for people with disabilities. The method used in this research is a type of qualitative descriptive research with a phenomenological approach. The data used were obtained through observation and documentation. Banking financial services provide convenience to every service user, including people with disabilities, this is a special concern for every banking financial service provider. With the digital era of industry 5.0, it can be a step in innovating to provide services. The phenomenon that becomes an obstacle "in the future is that service providers must put aside income receipts and "prioritize services to every banking customer, including people with "disability."